2017
DOI: 10.1080/13561820.2017.1356810
|View full text |Cite
|
Sign up to set email alerts
|

Student experiences of interprofessional simulation: Findings from a qualitative study

Abstract: Interprofessional simulation provides healthcare profession students an opportunity to collaborate in a team. The purpose of this study was to examine student perspectives of an interprofessional simulation experience within the fields of nursing, physical therapy, nutrition, and social work. An exploratory case study design was employed, using open-ended interview questions post-simulation to generate information about the student's perceptions of the experience. Based on the content analysis of reflection ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 7 publications
3
24
1
6
Order By: Relevance
“…The experiences obtained from interprofessional simulations have been mostly positive (Costello et al, 2018;Ivey, Bowman, & Lockeman, 2018;Jakobsen et al, 2018;Popkess et al, 2017;Roberts & Goodhand, 2018;Zamjahn et al, 2018), and there have been few differences in the participants' satisfaction levels based on different occupational groups or sectors. However, in a study by Jakobsen et al (2018), medical students were found to learn more than nursing students about the leader's role during a simulation.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 3 more Smart Citations
“…The experiences obtained from interprofessional simulations have been mostly positive (Costello et al, 2018;Ivey, Bowman, & Lockeman, 2018;Jakobsen et al, 2018;Popkess et al, 2017;Roberts & Goodhand, 2018;Zamjahn et al, 2018), and there have been few differences in the participants' satisfaction levels based on different occupational groups or sectors. However, in a study by Jakobsen et al (2018), medical students were found to learn more than nursing students about the leader's role during a simulation.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The participants in interprofessional simulations have appreciated the related opportunity for learning in situations that resemble reality (Costello et al, 2018;Hovland, Whitford, & Niederriter, 2018;Naismith et al, 2020) and allow applying theory to practice (Hovland et al, 2018). Professional simulation training has supported the learning of high-quality care and the development of the learners' professional growth (Roberts & Goodhand, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…A formação interprofissional é eficaz para o desenvolvimento de profissionais competentes, possibilitando: um estilo de educação que permite o trabalho em equipe, a integração e a flexibilidade da força de trabalho, além da reflexão dos aprendizes sobre a necessidade de domínios de conhecimentos, habilidades e atitudes para que possam atuar e contribuir para a socialização entre os profissionais 6,7 . Também permite a discussão de temas que, normalmente, apenas margeiam os conteúdos curriculares de uma forma pouco prática, como: profissionalismo, liderança, comunicação, tomada de decisão, administração e gerenciamento, educação permanente, ética e bioética, e juízo de crenças e valores pessoais e corporativos, compondo as competências gerais (ou comuns a todos os profissionais da saúde) da prática interprofissional compartilhada.…”
Section: Introductionunclassified